2013
DOI: 10.1080/14459795.2013.826709
|View full text |Cite
|
Sign up to set email alerts
|

Explaining the performance of online sports bettors

Abstract: This article reports the results of an online survey conducted among a sample of 161 online sports bettors in which their return-on-investment (ROI) performance as computed on the basis of their last 20 bets was used as the main dependent variable. A regression analysis showed that the online gamblers' ROI performance is positively associated with their experience in sports betting, the degree of information search and analysis performed prior to betting, and their propensity to consider that events that happe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 34 publications
(55 reference statements)
0
5
0
2
Order By: Relevance
“…Because research has shown that the relationship between arousal and recall is probably not linear (e.g., Tavassoli et al, 1995), it would be relevant to test the interplay between viewing environment (and, consequently, felt presence), sponsor-event congruence, and arousal in the context of high stakes sporting events (e.g., a playoff or a Stanley Cup game). High stakes games are notoriously unpredictable, to the extent that seasoned gamblers strategically shun them (d' Astous and Di Gaspero, 2013). In turn, the unpredictability of a high stakes game stimulates arousal as empirically shown by Humphreys (2002) and Walliser (1996).…”
Section: Limitations and Avenues For Further Researchmentioning
confidence: 99%
“…Because research has shown that the relationship between arousal and recall is probably not linear (e.g., Tavassoli et al, 1995), it would be relevant to test the interplay between viewing environment (and, consequently, felt presence), sponsor-event congruence, and arousal in the context of high stakes sporting events (e.g., a playoff or a Stanley Cup game). High stakes games are notoriously unpredictable, to the extent that seasoned gamblers strategically shun them (d' Astous and Di Gaspero, 2013). In turn, the unpredictability of a high stakes game stimulates arousal as empirically shown by Humphreys (2002) and Walliser (1996).…”
Section: Limitations and Avenues For Further Researchmentioning
confidence: 99%
“…One of these three studies revealed that 62.5% of gamblers spent from 157 to 314$ CAD per session, and half of them gambled many times per week (Noriega & Lin, 2003). Another study that reported specific data for gambling habits of SEB revealed that they bet on average 19 times per week, where each bet was valued around 10$ CAD (D'Astous & Di Gaspero, 2013).…”
Section: Sports Events Bettors (Seb)mentioning
confidence: 99%
“…One study rather indicated the opposite for financial gains: there was a positive association between gamblers' experience (measured subjectively) and financial investment returns ([Sum of gains-Sum of bets]/Sum of bets) X 100). The sample of SEB obtained investment returns of 11.1% on the average of their 20 last bets (D'astous & Di Gaspero, 2013).…”
Section: Sports Events Bettors (Seb)mentioning
confidence: 99%
“…B. bei Rückmeldungen zur Güte der eigenen Prognosen) [13] oder die Analyse von Prozessen der Informationsverarbeitung (z. B. bei Online-Sportwetten) [14]. Eine weitere Möglichkeit zur empirischen Bestimmung des Geschicklichkeitsanteils besteht in der Durchführung von Tippstudien unter Realbedingungen, bei denen einzelne Personengruppen mit unterschiedlicher Expertise gegeneinander oder gegen den Zufall antreten und den Ausgang von zukünftig stattfindenden Sportereignissen vorhersagen.…”
Section: Merksatzunclassified